2018
DOI: 10.1007/s10433-018-0487-y
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness amongst older people in Europe: a comparative study of welfare regimes

Abstract: Previous research implies that the extent of welfare state regime provision plays an important indirect role in the prevalence of loneliness in later life. The aim of this study was therefore to assess the association between quality of living conditions and level of social integration indictors and the absence of loneliness in five different welfare regimes. By incorporating welfare state regimes as a proxy for societal-level features, we expanded the micro-level model of loneliness suggesting that besides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 35 publications
3
46
0
7
Order By: Relevance
“…Results showed that social relations were the most important predictor of happiness in Southern nations, and were also significantly related to perceived health in Western and Central and Eastern European nations. Sufficient empirical evidence exists to show the impact of positive social interaction and support on health and quality of life among older adults (e.g., Andrews & Withey, 2012 ; Huxhold et al, 2013 ; Netuveli et al, 2006 ; Nyqvist et al, 2019 ). However, this may not always the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that social relations were the most important predictor of happiness in Southern nations, and were also significantly related to perceived health in Western and Central and Eastern European nations. Sufficient empirical evidence exists to show the impact of positive social interaction and support on health and quality of life among older adults (e.g., Andrews & Withey, 2012 ; Huxhold et al, 2013 ; Netuveli et al, 2006 ; Nyqvist et al, 2019 ). However, this may not always the case.…”
Section: Discussionmentioning
confidence: 99%
“… Samuel and Hadjar (2016) argued that advanced and larger welfare states (e.g., social-democratic welfare-state) help facilitate more equitable distribution of well-being in aging populations. It is also often observed that older adults’ isolation is significantly related to different cultural norms and welfare regimes; prevalence of loneliness in older adults is significantly higher in Southern and Eastern Europe compared to their counterparts in Western and Northern Europe ( Hansen & Slagsvold, 2016 ; Nyqvist et al, 2019 ). All of this suggests that a significant difference would exist in the association of social exclusion and subjective well-being in European older adults.…”
mentioning
confidence: 99%
“…Similarly, while three articles in our review analysed living in, or entry to, residential care, no articles considered social care more broadly, such as the receipt of home help, day care, respite care etc. Cross-sectional research has found that older adults in receipt of social care have higher levels of social loneliness (Dahlberg & McKee, 2014), while cross-country comparisons suggest that welfare states can enable social participation and reduce loneliness (Nyqvist, Nygard, & Scharf, 2019) and that differences regarding, e.g. material deprivation and lack of access to health care are associated with differences in loneliness (Morgan et al, 2021).…”
Section: Research Focus and Gapsmentioning
confidence: 99%
“…27,28 Some studies have also shown that older adults from more individualistic societies 29 and societies with better welfare regimes like those in Northern and Central Europe, are less likely to suffer from loneliness and its consequences than those in more collectivistic cultures with lower levels of social protection in Southern and Eastern Europe. 30 Also, when compared to older adults from other European regions, the Spanish elderly have longer nighttime sleep, shorter daytime naps, and later bed and wake up times. 31 Given these particularities, we aimed to evaluate whether social network was prospectively associated with changes in sleep quality and sleep duration over time in community-dwelling older adults in Spain.…”
Section: Introductionmentioning
confidence: 98%